Penerapan model problem based learning berbantuan socio scientific issue (SSI) untuk meningkatkan kesadaran lingkungan pada pembelajaran IPAS peserta didik kelas V sekolah dasar - Exa, Hasna Nabila; Daryanto, Joko (Universitas Sebelas Maret, 2026)
This study attempts to provide a description of application of problem-based learning model based on Socio Scientific Issues (SSI) that can increase environmental awareness. This study utilizes the Classroom Action Research (CAR) method. The study was conducted with all students from grade V A at SD Negeri Rejosari Surakarta as subjects. The data used are qualitative and quantitative data with data collection techniques using observation, interviews, questionnaires, and documentation. The validity test technique uses triangulation of sources and techniques. Data analysis uses data analysis techniques proposed by Miles and Huberman, namely data collection, data reduction, data presentation, and conclusion drawing or verification. The results of this study prove that the model can increase students' environmental awareness which is reflected in the increasing understanding of environmental issues, empathy and responsibility, and environmentally conscious behavior in everyday life.